Hydrogen Sulfide Detection by Sensors Based on Conductive Polymers: A Review - Duc, Caroline; Boukhenane, Mohamed-Lamine; Wojkiewicz, Jean-Luc; Redon, Nathalie (Frontiers in Materials, 2020)
Coming from natural and anthropogenic sources, hydrogen sulfide gas (H2S) is a smelly hazardous substance at sub-ppm level, which can lead to poisoning deaths at higher concentration. Researchers have been working for decades to design sensors with sufficient/good/robust metrological properties and good stability in order to monitor and control in real-time the risk associated to this gas. Among the devices proposed, chemiresistive sensors based on conductive polymer appear as a good alternative to the most common solutions such as electrochemical and optical sensors. They present various advantages in term of design (easy fabrication, easy tuning of physical and chemical properties, low cost, etc.) and performances (good sensitivity, good reproducibility, room temperature operation, short response time, etc.). In this review, we summarize the progresses made on conductive polymers sensors dedicated to H2S detection, including the performance of the different materials and sensing mechanisms. Finally, we identify the limitations of these sensors and highlight the most promising approaches to enable the use of these technologies in real-world applications.